Insurance company’s salespersons’ lead qualification skills and salespersons’ performance: moderated-mediation model of salespersons’ adaptive selling behavior and salespersons’ gender - Mwesige Richard; Bonuke Ronald; Situma Claire; Kabasinguzi Brenda (Cogent Business & Management)
This study aimed to discover the intervening role of Salesperson Adaptive Selling Behavior (SPASB) in the relationship between Salesperson Lead Qualification Skills (SPLQS) and Salesperson Performance (SP), in addition to the potential moderating effect of Salesperson Gender (SPG) on this relationship in the insurance industry in Uganda. A total of 346 salespeople in the Ugandan insurance industry were identified using approportionate stratified simple random sample technique. Data were collected using a self administered questionaire, then descriptive statistics, correlation analysis, factor analysis, and conditional process analysis were employed to analyze the data. The results showed that SPLQS and SP are partially mediated by SPASB. The mediating influence is contingent on the level of SPG, with a stronger mediation effect observed at higher levels of gender equality. By adding to the body of current literature, this study examines the complex relationships between SPLQS, SPASB, SP, and SPG. These findings highlight the importance of considering the role of SPASB and gender dynamics in optimizing SP. The results provide valuable insights for sales organizations to develop strategies to enhance SP in uncertain business environments. Additionally, this study sheds light on the gender-specific factors that influence SP, challenging traditional stereotypes in the sales profession.